ARTIFICIAL INTELLIGENCE (AI)-BASED ENTERPRISE BUSINESS INFORMATION MANAGEMENT ARCHIVE SYSTEM - Rofiyana, Rofiyana; Mursid, Mansur Chadi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The purpose of this study is to describe an artificial intelligence (AI)-based corporate information management archive system. The use and technological advancement of artificial intelligence in corporate information management archiving systems is the primary emphasis of this research. This study employs a qualitative methodology that generates descriptive data through written text or behavior observations and takes a comprehensive approach to the situation and people. This article's research methodology blends empirical analysis with a study of the literature. This study's primary focus is on the state of artificial intelligence technology research and application in commercial data archive management systems. Business information management archive systems that use artificial intelligence (AI) technology provide creative ways to handle ever-more complicated corporate data. AI makes it possible to automate the process of effectively storing, categorizing, searching, and analyzing data, which raises the precision and efficacy of information management. Furthermore, this technology may enhance the security and openness of company data, identify irregularities, and offer strategic advice. AI has the potential to be a game-changing instrument that supports corporate objectives in the digital age if it is regularly adjusted and the appropriate policies are developed.